Peran guru dalam pelatihan seni tari untuk meningkatkan kepercayaan diri siswa SDN 02 Sungai Laur Kalimantan Barat - Ahmad Al Fajar; Poppy Indriyanti (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
The purpose of this research is to describe: 1) the implementation of dance training to increase students self-confidence, 2) supporting and inhibiting factors in the implementation of the teacher's role in dance training; 3) solutions made in overcoming obstacles from implementing the teacher's role in dance training. This research uses the descriptive analysis method. Data collection methods in this study: observation, interviews, and documentation. The results of the research show: 1) The implementation of dance art training to increase students' self-confidence is carried out in the thematic lessons of SBdP content; 2) Factors supporting the implementation of the teacher's role in dance training are the enthusiasm and spirit of students who can memorize movements quickly, while the inhibiting factors are: some students who feel embarrassed when practicing dance in front of their friends, and the existence of the covid pandemic - 19 causing dance training to be delayed or even stopped, as well as inadequate facilities and infrastructure; 3) The solution that can be done is to continue to practice dance by utilizing existing facilities and infrastructure, while online learning during the Covid-19 pandemic was carried out by asking students to learn dance from home by their cellphones, in addition to giving assignments make their dance moves to increase self-confidence in students.